Impact of cation-based mineral supplement characteristics on dairy farmer’s adoption: Insights from a field trial - GOYAL, SHASHIKANT; SANKHALA, GOPAL; DATT, CHANDER; MEENA, B S; MONDAL, GOUTAM; MAITI, SANJIT; R, SENDHIL; RAI, CHANDAN KUMAR (The Indian Journal of Animal Sciences, 2024)
The attributes of innovation encompass the qualities, traits or characteristics inherent in an object reflecting the relative benefits of a novel idea. Assessing these attributes during the early stages of innovation within farmer management practices can offer valuable insights to the scientific community, enabling the formulation of policies to expedite farmer adoption. This study examined the perceived attributes of Cation-based Mineral Supplement (C-bMS). The research findings indicated that C-bMS demonstrates a moderate relative advantage (82.49%) compared to other mineral supplements in mitigating ruminal acidosis. It is highly compatible (80.84%), easy to comprehend and utilize, readily trialable (73.75%) with observable effects of feeding (78.75%), and predictable benefits (87.92%) for dairy farmers. Feeding C-bMS helps alleviate negative energy balance, increasing feed intake which in turn boosts milk production, ultimately reducing production costs by preventing ruminal acidosis and potentially doubling dairy farmers’ income. Raising general awareness among dairy farmers about ruminal acidosis, the consequences of negative energy balance, and the advantages of feeding C-bMS can be achieved through effective extension methods such as demonstrations and exhibitions.